Understanding the experience of the mothers’ ability to take care of their preterm infants related to in-hospital and post-discharge: a qualitative content analysis - Saleheh Tajalli; Soroor Parvizy; Abbas Ebadi; Fateme Zamaniashtiani; Carole Kenner (BMC Pediatrics)
Abstract Background Preterm infants may experience many health and developmental issues, which continue even after discharge from the neonatal intensive care unit. Once home, the mother, as a non-professional and the primary caregiver will be responsible for the essential care of her preterm infant. Purpose Understanding the take care ability in mothers with preterm infants. Methods The content analysis method was used. The data were collected using in-depth and semi-structured interviews from April 2021 to February 2022. Eleven mothers, two fathers, two grandmothers, one neonatal nurse, and two neonatologists with a mean age of 36.05 ± 10.88 years were selected using purposeful and snowballing sampling in Tehran, Iran. Allocating adequate time for data collection, gathering data through different methods, peer checking by two qualitative researchers, long interaction with the settings, maximum variation sampling, appropriate quotations, and showing the range of facts fairly and honestly were considered to ensure the trustworthiness of this study. The data were analyzed through Lindgren et al.’s approach using MAXQDA software. Results Based on the findings and participants’ experiences in 18 deep interviews, the mothers with desirable care ability have adequate ability as described by 17 subcategories and are categorized into five dimensions. The care ability of the mothers of preterm infants upon neonatal intensive care unit discharge consisted of five categories including maternal identity, infant’s needs, cognitive ability, technical ability, and psychological ability. Implications for practice and research In the mothers of preterm infants, maternal identity and the infant’s needs are antecedents of the care ability concept. The care ability of the mothers with preterm infants is distinct from those of other caregivers. This is a multi-dimensional concept and trait related to maternal cognitive ability, technical ability, and maternal psychological ability. Professional neonatal nurses should assess their care ability from multiple perspectives: cognitive, technical, and psychological abilities. They should be considered in designing empowerment and engagement programs for the improvement of the care ability of the mothers of preterm infants. Both mothers and professional neonatal nurses should take responsibility for improving the mothers' ability to take care of their preterm infants.